2005
DOI: 10.1074/jbc.m506339200
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of Cg-emb in Corynebacterianeae Leads to a Novel Truncated Cell Wall Arabinogalactan, whereas Inactivation of Cg-ubiA Results in an Arabinan-deficient Mutant with a Cell Wall Galactan Core

Abstract: The cell wall of Mycobacterium tuberculosis has a complex ultrastructure that consists of mycolic acids connected to peptidoglycan via arabinogalactan (AG) and abbreviated as the mAGP complex. The mAGP complex is crucial for the survival and pathogenicity of M. tuberculosis and is the target of several anti-tubercular agents. Apart from sharing a similar mAGP and the availability of the complete genome sequence, Corynebacterium glutamicum has proven useful in the study of orthologous M. tuberculosis genes esse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
261
2

Year Published

2006
2006
2010
2010

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 136 publications
(269 citation statements)
references
References 46 publications
6
261
2
Order By: Relevance
“…Indeed, Liu and Mushegian (29) identified 15 members of the GT-C superfamily, representing candidates involved in the biosynthesis of cell wall related glycans and lipoglycans in M. tuberculosis. We have continued our earlier studies (9,16,19) to identify genes required for the biosynthesis of the core structural elements of the mAGP complex in Corynebacterianeae by studying mutants of C. glutamicum and the orthologous genes and enzymes of M. tuberculosis. Herein we present Rv3805c as a new arabinofuranosyltransferase of the GT-C superfamily that is responsible for the transfer of Araf residues from DPA to the arabinan domain to form terminal ␤(1 3 2)-linked Araf residues, which marks the "end point" for AG arabinan biosynthesis before decoration with mycolic acids.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Indeed, Liu and Mushegian (29) identified 15 members of the GT-C superfamily, representing candidates involved in the biosynthesis of cell wall related glycans and lipoglycans in M. tuberculosis. We have continued our earlier studies (9,16,19) to identify genes required for the biosynthesis of the core structural elements of the mAGP complex in Corynebacterianeae by studying mutants of C. glutamicum and the orthologous genes and enzymes of M. tuberculosis. Herein we present Rv3805c as a new arabinofuranosyltransferase of the GT-C superfamily that is responsible for the transfer of Araf residues from DPA to the arabinan domain to form terminal ␤(1 3 2)-linked Araf residues, which marks the "end point" for AG arabinan biosynthesis before decoration with mycolic acids.…”
mentioning
confidence: 99%
“…The biosynthesis of AG involves the formation of a linear galactan chain with alternating ␤(1 3 5) and ␤(1 3 6)-D-galactofuranosyl (Galf) residues of ϳ30 residues in length from the specialized "linker unit," L-Rhap-(1 3 4)-␣-D-GlcNAc (20,21). MALDI-TOF mass spectrometry (MS) analyzes of per-Omethylated AG of C. glutamicum deleted of its single arabinofuranosyltransferase, Cg-emb, revealed that the 8th, 10th, and 12th Galf residue possessed singular Araf residues (9). These specific Araf residues were recently shown to be transferred by a specialized arabinofuranosyltransferase AftA, whose gene in all Corynebacterianeae analyzed to date is adjacent to the emb cluster (19).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…EmbR has originally been cloned from Mycobacterium avium in the context of identifying genes that confer ethambutol resistance (13). Ethambutol, a front-line antitubercular drug, targets a set of membraneembedded arabinosyltransferases (M. avium EmbA and -B and Mtb EmbC, -A, and -B) that are involved in arabinogalactan and lipoarabinomannan biosynthesis, a critical component of the mycobacterial cell wall (13)(14)(15)(16)(17). In M. avium, the embR gene is located upstream of embA and -B, leading to the hypothesis that embR might control expression of the Emb arabinosyltransferases.…”
mentioning
confidence: 99%